Offline perception: an introduction - Fazekas, Peter; Nanay, Bence; Pearson, Joel (Philosophical transactions of the Royal Society of London. Series B. Biological sciences)
Experiences that are self-generated and independent of sensory stimulations permeate our whole life. This theme issue examines their similarities and differences, systematizes the literature from an integrative perspective, critically discusses state-of-the-art empirical findings and proposes newtheoretical approaches. The aim of the theme issue is to foster interaction between the different disciplines and research directions involved and to explore the prospects of a unificatory account of offline perception in general. This article is part of the theme issue 'Offline perception: voluntary and spontaneous perceptual experiences without matching external stimulation'.